Peran Pencegahan Fraud Memoderasi Pengaruh Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Agustina Indriani (STIE Jambatan Bulan, 2021)
This study aims to examine the effect of the government's internal control system and internal control on fraud prevention and its implications for the quality of regional financial reports. The sample used in this study were 89 respondents to local government employees in Bogor and Depok. The test is done using multiple linear regression analysis, the data is processed using SPSS. The results show that the influence of the government's internal control system has a positive effect on fraud prevention, while internal control has no effect on fraud prevention, while fraud prevention has a positive effect on the quality of financial reports. The Government's Internal Control System has a negative effect on the Quality of Regional Financial Reports and Internal Control has a positive effect on the Quality of Regional Financial Reports. The government's internal control system has an indirect effect on the quality of regional financial reports through fraud prevention. Internal control has a direct effect on the quality of regional financial reports through fraud prevention. Fraud prevention has a greater influence on the quality of regional financial reports. The internal control system of a business entity is strong, so the possibility of errors and fraud can be minimized. This means that the more successful the prevention of fraud, the quality of regional financial reports will increase